Simulating infection prevention and control through virtual reality: a vehicle for equity, diversity, and inclusivity in Africa - Botha, Benjamin S.; Hugo-van Dyk, Lizemari; Nyoni, Champion N. (Frontiers in Education, 2023)
Endemics in Africa are prominent, especially in countries with low income and inadequate infection prevention and control (IPC) measures. Additionally, poorly trained nurses negatively influence infection-related indicators, and these nurses may require re-training. Re-training is expensive, and due to limited resources, healthcare institutions in Africa may not have the opportunity for their nurses to be re-trained in a critical competence such as IPC. Simulation-based education, including virtual reality (VR), has shown numerous benefits in acquiring critical thinking, communication, and clinical skills. However, VR has been reserved for healthcare education in the global north. Also, no educational programmes currently exist that harness the power of VR in a low-resource context such as Africa. We argue that VR is a possible low-cost simulation modality that can create standardised training resulting in equitable, diverse, and inclusive IPC education for nursing students. However due to a lack of technological training and ongoing support, low to middle-income countries often end up failing to implement the interventions over a longer term than the initial investment. Authors like Hofstede et al. (2010) identified dimensions causing problems between various cultures, which might restrict the implementation of newer technologies in a diverse, equitable, and inclusive manner. The design and implementation of an educational innovation must address and integrate the cultural dimensions of the targeted context. Embracing, understanding, and respecting the variations in local culture within African universities is essential to inclusive and diverse education practices and the subsequent designing and implementation of educational innovation such as VR.